Hotel Guests’ Perceptions of Environmentally Friendly Practices in Jordan - RAWASHDEH, Akram Atef; AL-ABABNEH, Mukhles Mansour (Journal of Environmental Management and Tourism; Vol 12 No 1 (2021): JEMT 1(49) Spring 2021DO - 10.14505/jemt.v12.1(49).09, 2021)
Tourism still generates negative effects on the environment that consequently objected the green practices in hotels; therefore, this study comes to measure the perception of international guests towards green practices in the Jordanian hotels. This study considers the first attempt that linked the tourists' perceptions toward green practices in hotels and their willingness to stay in eco-label hotels in Jordan. The study relied on the quantitative approach to measure the level of those practices as 270 questionnaires were collected during the period from March to September 2019. The questionnaire included questions on 7 eco-label criteria (Green hotel certification, Energy, Water, Waste and Purchasing Management, Community support and Customer education) comprising all areas of hotel operations, and 3 statements to measure hotel guests’ guests’ willingness to stay in eco-label hotel. The statistical analysis was performed using SPSS program version 21. The study found a positive but moderate correlation between tourists' perceptions towards environmental practices and their stay in eco-hotels. In addition, the various dimensions of environmental practices were positively related to tourists staying in an environmentally friendly hotel. This is one of the first studies that linked tourists' perceptions towards green practices in the hotels and their willingness to stay in eco-label hotel.